On the role of regulatory standards: Specification and some empirical evidence from motor vehicle fuel economy - Zachariadis, Theodoros (My University, 2007)
This paper proposes a simple model to evaluate the role of regulatory controls. It is formulated so as to enable drawing empirical conclusions on the basis of usual hypothesis tests. Three potential roles of standards are examined: they can act as penalties for non-compliant firms, as norms to which all firms converge, and as controls with cumulative impact over time. I test this specification focusing on automobile fuel economy (CAFE) standards that have been imposed in the US since 1978, using annual data from each major auto manufacturer. Results show that CAFE rules, functioning mainly as penalties, have been an important determinant of car fuel consumption. The hypothesis that standards acted also as norms is rejected. Finally, the automobile industry as a whole became less constrained by regulations over the years because of stagnating CAFE standards since 1990 and progress in vehicle technology.
Keywords: Regulation; Compliance; Penalty; CAFE; Automobile